PERKEMBANGAN KURIKULUM DI INDONESIA DARI KLASIK KE MODERN - Azhar (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2020)
The concept of the curriculum continues to develop and change from year to year in accordance with the development and needs of society. In Indonesia there have been several curriculum changes since 1947 to 2021. For this reason, it is necessary to study changes. This study uses the literature method by making the source of information from various literatures. Then categorized, analyzed and conclusions drawn. There are several findings from this study, namely curriculum development in Indonesia has been carried out since 1947, which was followed by changes or improvements in the following years, namely: 1952, 1964, 1968, 1975, 1984, 1994, 2004, and 2006. on purpose and adopts an integrative approach. The 1984 and 1994 curricula were oriented towards instructional and material goals with an active student learning approach. The 2004 curriculum is called the Competency-Based Curriculum which focuses on the ability according to predetermined standards. KTSP is given full authority to the school to compile its education plan by referring to the standards that have been set. Finally, the 2013 Curriculum which is oriented towards the development of cognitive, affective and psychomotor competencies.